2014
DOI: 10.7183/2326-3768.2.3.222
|View full text |Cite
|
Sign up to set email alerts
|

Regional-Scale Archaeological Remote Sensing in the Age of Big Data

Abstract: With the ever expanding quantity of high-resolution aerial and satellite imagery available to archaeologists, numerous researchers have sought to address this "big data" challenge by developing automated methods to aid in the discovery and mapping of archaeological sites and features. This paper reviews several notable efforts to create automated discovery tools, including both spectral and object-based approaches, and highlights the difficulties these projects have encountered. Arguing instead for the critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 42 publications
1
79
0
1
Order By: Relevance
“…Remote sensing is not always the most appropriate method for identifying archaeological sites. Even the application of labour intensive remote-sensing visual analysis or 'brute force' methods as Casana [17] (p. 231) has termed them is in some regions simply not the best option for large-scale site detection and monitoring. For example, trials carried out by the EAMENA team using their methodology in Kuwait revealed that large numbers of 'known' archaeological sites could not be identified via imagery, even when given precise locations for these sites.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Remote sensing is not always the most appropriate method for identifying archaeological sites. Even the application of labour intensive remote-sensing visual analysis or 'brute force' methods as Casana [17] (p. 231) has termed them is in some regions simply not the best option for large-scale site detection and monitoring. For example, trials carried out by the EAMENA team using their methodology in Kuwait revealed that large numbers of 'known' archaeological sites could not be identified via imagery, even when given precise locations for these sites.…”
Section: Discussionmentioning
confidence: 99%
“…For Middle Eastern landscapes in particular, the declassification in the 1990s of Cold War satellite photography collected in the 1960s-1970s revolutionised this sub-field. This facilitates the mapping of features, especially as many sites have been damaged or destroyed during phases of agricultural and urban expansion in the last 40 years [15][16][17][18][19]. In North Africa, projects focusing on Libya initially made use of the Landsat sensors which have been collecting data since the 1970s (e.g., the Libyan Valleys Project, [20]).…”
Section: Remote Sensing and Heritage Recording In The Mena Regionmentioning
confidence: 99%
See 3 more Smart Citations